Behavioral evidence of oxidative stress derived from haematophagy in the ocellar system of Rhodnius prolixus Stal, 1859 red-eyed mutants (2017)
The photonegative responses to light stimulation in Rhodnius prolixus (Reduviidae, Triatominae) is modulated by compound eyes and ocelli. Screening pigments in the visual system have been shown to protect the cellular structures from oxidative stress damage generated by ingesting blood and light stimulation. Red-eyed mutants of Rhodnius prolixus lack screening pigments in compound eyes and ocelli and are exposed to oxidative stress. Experiments with Rhodnius prolixus and Triatoma infestons red-eyed mutants reared from first nymphal stage have shown a damage in the retina of the compound eyes and a decrease in the photonegative responses to light stimulation. Having in mind that ocelli are only present in the imaginal stages, we designed a group of experiments to test a possible damage of ocelli by oxidative stress mediated by blood ingestion in Rhodnius prolixus red-eyed mutants and wild type. We carried out behavioral experiments to evaluate the photonegative responses in adults exposed to different treatments including covering compound eyes or ocelli, and different blood feeding treatments in order to test Our hypothesis. Our results show that ocelli in adults of Rhodnius prolixus can modulate the photonegative responses in red-eyed mutants better than the compound eyes. In addition, a decrease in photonegative responses was evident when the red-eyed mutants were fed with blood for up to four weeks. The ocelli in Rhodnius prolixus can be cataloged as a feedback visual system in the photonegative responses to light stimulation and screening pigments in the visual system are playing an important role to prevent damage by oxidative stress due to blood feeding.